PENGARUH GERAKAN PEMURNIAN AGAMA TUANKU NAN RENCEH TERHADAP KEBUDAYAAN MINANGKABAU DI KECAMATAN TILATANG KAMANG KABUPATEN AGAM 1803-1838 - Nisa TM, Ifni Aulia Nisa TM Aulia; ', Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : The district Tilatang Kamang there are various traditions that deviate from religion norms. Customs and traditions have clung so hard so to be abolished. The ulama seeks to advise the public to follow the Islmanic Shari’a, but the fact is many people who do not want to listen to that advice, until a religious figure Tuanku Nan Renceh initiate new ideas to change people’s traditions with harsh and radical teachings.This study aims to determine the background (biography) Tuanku Nan Renceh, to know the culture and traditions of Tilatang Kamang society before and after the entry of the renewal, to know the cultures deviant who eradicated by Tuanku Nan Renceh, to know mindset Tuanku Nan Renceh about the culture to deviate, to find out what Tuanku Nan Renceh efforts in making changes to the system and habits of the people who have strayed of religious norms and customs norms prevailing in society.The theory used in this study is religious purification movement theory, the theory of religion, forms of movement of religious purification, and cultural theory. This study uses historical and documentary research. Data collection techniques in this study is the literature, documentation, comparative studies will then be deduced.The results showed that Tuanku Nan Renceh is known as the man who led a religious movement in Tilatang Kamang to change the tradition and culture of the people who deviate. As an Islamic religious leader, Tuanku Nan Renceh implement radical teachings and did not hesitate to act against violence against society so successfully eradicate some deviant culture, the pattern wahhabi teachings of mecca.Keywords: Culture, Religion, Tuanku Nan Renceh